Tangible Interaction Design: Preparing Future Designers for the Needs of Industrial Innovation. (2015) - Wang, Stephen Jia; Moriarty, Patrick; Wu, Shi-Zhong
Abstract: The last decade has seen a remarkable uptake of interactive systems, products and services. Their design requires a shift from the traditional skills of material product-focused designers. We argue that the creativity in designing these information-enriched products needs to stress both physical properties and interactivity. The challenge is finding an educational approach that can equip industrial design graduates with stronger creativity instead of overstating the awareness of new technologies. This approach should extend rather than replace the knowledge, skills and experience from traditional design education. Using Monash University as the test bed, Tangible Interaction Design Education (TIDE), the cornerstone of this pedagogical model, provides an approach that blurs the boundaries between tangible objects and intangible services.